ROUND THE ISSUE OF COINAGE OF THE NORTHEASTERN TRANSCAUCASIAN KHANATES IN THE SECOND HALF OF THE 18-TH CENTURY - Mkhitaryan Gohar (Bulletin of the institute of oriental studies (Online), 2016)
In the second half of the 18-th century the Northeastern Transcaucasian Khanates have continued the Iran’s state monetary policy traditions. The coinage historical analysis reveals, that Transcaucasian Khans were using this function to show their political stance towards Iran. And they were duing a certain diplomacy, which is consistent with the Northeastern Transcaucasian Khan’s maneuvers policy.